2003
DOI: 10.1111/j.1471-0528.2003.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality: only 42 days?

Abstract: aObjective A maternal death is defined by WHO as 'the death of a woman while pregnant or within 42 days of termination of pregnancy. . .'. The origin of the 42 days is no longer clear. In developing countries, the burden imposed by pregnancy and birth on a woman's body may extend beyond 42 days as pregnancyrelated anaemia can persist for longer and vaginal haemorrhaging and risk of infections are not necessarily over after six weeks. We therefore examined duration of excess mortality after delivery in rural Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…20 The adequacy of this definition has been questioned. 21 In this study, the inclusion of late deaths added 17% to 49% to the pregnancy-related mortality ratio. Suicide in a context of postpartum depression and deaths due to peripartum cardiomyopathy occurred preferentially after 42 days postpartum and were the main causes of late pregnancy-related deaths in the 4 regions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…20 The adequacy of this definition has been questioned. 21 In this study, the inclusion of late deaths added 17% to 49% to the pregnancy-related mortality ratio. Suicide in a context of postpartum depression and deaths due to peripartum cardiomyopathy occurred preferentially after 42 days postpartum and were the main causes of late pregnancy-related deaths in the 4 regions in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that maternal deaths due to psychiatric illness have been under‐reported, partly because of misclassification of suicides as incidental deaths, and partly because of under‐reporting of late maternal deaths 3 . Late maternal deaths are more difficult to identify, as they often occur after women have ceased to attend maternity services.…”
Section: Classification Of Maternal Deathsmentioning
confidence: 99%
“…Where linkage studies of death and birth data have been performed, they have revealed an over‐representation of maternal deaths associated with suicide or psychiatric illness. Many of these deaths are not captured by routine data collection methods because they often occur after 42 days postpartum 3 , 4 . Thus, an Office of National Statistics (ONS) linkage study in the UK identified over 40 extra maternal deaths in the 1997–1999 triennium from suicide or violent causes, making suicide the leading cause of indirect maternal deaths once these cases were added to the NICE report statistics 5 , 6 .…”
Section: Incomplete Detection Of Maternal Deathsmentioning
confidence: 99%
“…[3][4][5] Until 2009, manual vacuum aspiration (MVA) was the only safe abortion technology in Nepal. Based on international evidence about the safety and efficacy of medical abortion Original Article in the absence of physicians.…”
Section: Introductionmentioning
confidence: 99%